Kualitas Pelayanan dan Kinerja Pegawai terhadap Kepuasan Masyarakat di Unit Pelayanan Terpadu Satu Atap Kementerian Ketenagakerjaan - Pramularso, Eigis Yani (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2020)
Abstract - The government as a public servant continues to strive to make positive perceptions by continuing to improve community satisfaction related to the various services that can be provided. Community satisfaction is strived to continue to increase by providing the best quality of service and continue to encourage employee performance to be more optimal in carrying out their duties. This study aims to determine the effect of service quality and employee performance on community satisfaction in the One-Stop Integrated Services Unit of the Ministry of Manpower. The sample in this study amounted to 45 people where the technique was taken by accidental sampling. The data collection method uses a questionnaire given to respondents who happened to come at the research location. Data analysis tools in this study used a regression test with a validity and reliability test conducted previously. The results of this study are simultaneous and partial service quality and employee performance have a significant influence on community satisfaction in the One-Stop Integrated Services Unit of the Ministry of Manpower where the calculated F value is 19,042 and sig 0,000. Keywords: Service Quality, Employee Performance, Community Satisfaction